Respect for ethical principles in professional work of nurses - Kostrzanowska, Zofia; Małek, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. Ethical principles are guidelines that help man in making the right moral choices both in professional work and in personal life. These rules get a special meaning in nurses’ work, i.e. in the profession that the main aim is “to serve the human life and health”. This particular kind of “service” , i.e. accompanying man throughout one’s life, both in health and illness, requires not only high professional qualities but also the right attitudes and moral behaviour. Therefore there is a need for deontological regulation of this type of behaviour and taking up research concerning the respect for ethical principles in professional work of nurses. Aim. The objective of the research was to learn about nurses’ knowledge in the field of ethical principles and the extent of respect for them in professional work. Material and methods. The research was carried out with the application of diagnostic survey and questionnaire. Empirical material was gathered by menas of a research tool designed by the author, i.e. a questionnaire. The research material comprises 100 nurses employed in Health Care Unit in Łuków. Results and conclusions. The majority of studied nurses (93,0%) had the knowledge of ethical principles but only 76,0% meets these principles at work where the main principle is responsibility (91,0%), respect for others (86,0%) and doing well (80,0%). The statistical analysis conformed a significant relationship between the knowledge of ethical principles and the respondents’ place of work (p = 0,0005).